3D Rotational Angiography After Non-Traumatic SAH - Ringelstein, A.; Mueller, O.; Mönninghoff, C.; Hahnemann, M. L.; Sure, U.; Forsting, M.; Schlamann, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: In about 15 % of patients with SAH no causative vascular lesions can be found in acute imaging with CTA and DSA. Usually, repeat DSA is mandatory and bears the usual risk of invasive angiography. The present study attempts to assess the diagnostic impact of 3 D rotational angiography in order to avoid repeat DSA.Materials and Methods: From January 2004 to December 2012, 649 patients with an acute non-traumatic SAH were examined. 91 patients with negative initial imaging diagnostics concerning the bleeding source were included in this study. These patients underwent a second angiography scan: 61 in 4-plane technique, and 30 with 2-plane technique and additional 3 D DSA. Two cohorts were compared: patients with repeat angiography in conventional 4-plane technique from 2004 to July 2008 and 2-plane technique with additional 3 D rotational DSA from 2008 to 2012. Statistical significance was verified by means of Fisher’s exact test.Results: In the second DSA scan, 4 aneurysms in 4 patients (4/91; 4.4 %) were found and treated subsequently. Within the first 4.5 years of this study, 401 patients with SAH were treated and 61 of them underwent repeat angiography (15.2 %) compared to 30 of 248 patients (12.1 %) in the last 4.5 years of this study. In the first group we found 3 aneurysms during repeat angiography, and in the second group we found 1. No significance was reached (p = 0.29) but there was a tendency towards higher diagnostic security using 3D-DSA.Conclusion: Using 3 D rotational DSA in initial imaging workup might help to reduce false-negative results concerning the bleeding source of acute SAH. At least because of this fact, 3 D rotational DSA should be part of the diagnostic workup after acute SAH.Key Points:• In 15 % of SAH patients no causative vascular lesion can be found using conventional DSA compared to 12 % using 3 D DSA.• Patients with perimesencephalic SAH and CT-negative SAH do not require repeat DSA.• 3 D DSA might help to avoid repeat DSA in SAH patients.Citation Format:• Ringelstein A, Mueller O, Mönninghoff C et al. 3D Rotational Angiography After Non-Traumatic SAH. Fortschr Röntgenstr 2014; 186: 675 – 679
Keywords: brain; angiography; aneurysm